Elevation in Circulating Soluble CD40 Ligand Concentrations in Type 2 Diabetic Retinopathy and Association with its Severity - Lamine, Laila Ben; Turki, Amira; Al-Khateeb, Ghada; Sellami, Nejla; Amor, Hagger B.; Sarray, Sameh; Jailani, Mohamed; Ghorbel, Mohamed; Mahjoub, Touhami; Almawi, Wassim Y. (Experimental and Clinical Endocrinology & Diabetes, 2020)
Background To investigate the relationship between changes in circulating soluble CD40 ligand (sCD40L) levels and the presence and severity of type 2 diabetic retinopathy (DR).Subjects and methods sCD40L plasma concentrations were measured in 205 type 2 diabetes (T2DM) patients without DR (DWR; n=50) and with DR (n=155), the latter subdivided into non-proliferative diabetic retinopathy [NPDR; n=98 (63.2%)], or proliferative retinopathy [PDR; n=57 (36.8%)] patients.Results Receiver operating characteristic analysis provided good discriminatory power for sCD40L as predictor of DR presence, with high sensitivity and specificity. Categorizing DWR and DR patients into sCD40L quartiles, based on sCD40L concentrations in T2DM without DR, demonstrated statistically significant gradual increase in DR risk with increasing sCD40L levels. sCD40L levels were significantly higher in DR compared to DWR patients. Plasma sCD40L levels differed significantly according to DR severity, and correlated with diabetes duration, dyslipedimea, nephropathy, and presence of DR, but not with gender, age, SBP, DBP, FPG, HbA1c, T2DM medications. Linear regression analysis confirmed the association of increased sCD40L levels with DR, independent of others parameters; mean plasma sCD40L levels differing significantly according to DR severity.Conclusion Plasma sCD40L levels were positively associated with DR. The significant finding here is that sCD40L levels can be predictors of DR severity.
Keywords: Diabetic retinopathy; obesity; sCD40L; type 2 diabetes